Incest. Penal-law and criminological aspects (Ius Novum, 2022)
The article discusses the statutory features of the offence of incest in the Polish Penal Codefrom 1997 (Article 201) and the results of empirical research carried out. Doubts were raised indoctrine about the rationalization of the prohibition of incest and the definition of the object ofprotection of this crime. The conduct that constitutes the actus reus as well as the subject andthe subjective side of the offence of incest were also analysed. The research material was thefiles of cases under Article 201 of the Penal Code registered in all public prosecutor’s officesin Poland in 2013–2014 (389 cases). Research was intended to was primarily to identify thecriminological picture of the offence of incest and its scale compared to total crime figuresin Poland and the policy of punishing. The next aim of the research was to characterise thefamilies, in which incestuous acts took place, and thus to answer the key questions in thiscontext: whether incest is a factor determining the so-called family pathology or maybe it isa phenomenon conditioned by it and whether it occurs spontaneously or is connected withsexual violence in the family. The results of the research show that the so-called “regularincest” (voluntary on both sides), qualified only under Article 201 of the Polish Penal Code,is relatively rare in the practice of the judiciary. Most cases of incestuous sexual relationswere combined with the crime type of sexual abuse of a minor or rape. These results seem toconfirm the thesis that incest is rarely the only committed offence, but is most often related todomestic sexual violence. They also support the thesis that incest is a phenomenon conditionedby already existing family dysfunctionality, not its cause.